The impact of timing of in utero marijuana exposure on fetal growth - Dodge, Phoebe; Nadolski, Katherine; Kopkau, Haley; Zablocki, Victoria; Forrestal, Kaya; Bailey, Beth A. (Frontiers in Pediatrics, 2023)
Objective: To examine whether timing of in utero marijuana exposure independently and negatively impacts fetal growth, and if these effects are global or specific to certain growth parameters. Study design: The two study groups were marijuana users (N=109) and a randomly selected control group of biochemically verified non-users (n=171). Medical records were manually reviewed for background and medical information. Results: After control for significant confounders, regression results indicated significant (p<.05) decrease in newborn weight following first trimester marijuana exposure only and following marijuana exposure throughout gestation compared to controls. There were also significant deficits in head circumference following marijuana exposure in the first and second trimester only and marijuana exposure throughout pregnancy. Newborn length was not predicted by marijuana exposure. Conclusions: Timing of marijuana exposure appears to play a key role in specific fetal growth deficits, with exposure throughout gestation most detrimental. However even first trimester exposure may result in decreased weight. Timing and amount of use could be confounded in this study as those who quit early in pregnancy may have been lighter users than those who continued throughout pregnancy. More research is clearly needed to better understand the role of amount and timing of in utero marijuana exposure in predicting different aspects of fetal growth, however, this study suggests that women should be encouraged to avoid marijuana use at any point in pregnancy.